Ji-Yong Lee, La gouvernance d’entreprise et l’hybridation : Le cas de l’Asie - Ji-Yong Lee (Revue de la Régulation)
Understanding of the changes in corporate governance lies at the heart of contemporary debates about transformation of capitalism. Asia is no exception to this phenomenon. Asia’s corporate governance has undergone significant changes since the financial crisis of 1997. Our study, based on the theory of institutional change, seeks to examine current transformations. The concept of corporate governance is viewed as being dependent on institutional environments in which the firm evolves. The analysis of the changes in corporate governance is therefore needed to understand institutional change.On this basis, we argue that the current transformation is experiencing a process of hybridization and we suggest a framework to understand ongoing corporate governance reform. Hybridization carries two opposed forces: drivers for change and resistance to change. The dynamic process of adaption of newly imported practices leads to new model adapted to local conditions. Our empirical analysis allows us to apprehend the diverse pattern of corporate governance in Asia even within the current context of adherence to the Anglo-Saxon model: we find three hybrid models and one other model which has not committed to the reform. We also study the sources of change and the factors that give rise to resistance. We provide an overview of the recent changes in corporate governance practice in Asian countries.